TRADIÇÕES DISCIPLINARES E TRADIÇÕES INTELECTUAIS NA TRAJETÓRIA DA CIÊNCIA POLÍTICA BRASILEIRA - Leite, Fernando (Caderno CRH, 2017)
O artigo trata do papel de tradições disciplinares e intelectuais na constituição da Ciência Política brasileira. Objetiva-se identificar as tradições que influenciaram as visões de grupos de intelectuais, sociólogos e cientistas políticos responsáveis pelos princípios que estruturaram a produção atual da disciplina. A partir de entrevistas e referências bibliográficas, identificamos tradições e suas oposições. Entendemos que a adesão e a incorporação desta ou daquela tradição pelos grupos envolvidos dependeram de suas trajetórias acadêmicas, marcadas por oposições orientadas no sentido de definir a disciplina, isto é, definir seu objeto legítimo e as abordagens consideradas mais apropriadas para estudá-lo. A produção dependeu de três grupos e visões: (i) humanística, associada aos intelectuais que estudavam temas políticos antes da institucionalização da Ciência Política; (ii) acadêmico-societal, associada à “escola sociológica paulista” e (iii) científico-politológica, associada ao grupo constituído em torno da UFMG e do Iuperj responsáveis pela institucionalização da Ciência Política no Brasil. DISCIPLINARY TRADITIONS AND INTELLECTUAL TRADITIONS IN THE TRAJECTORY OF THE BRAZILIAN POLITICAL SCIENCES ABSTRACT This article deals with the role of disciplinary and intellectual traditions in the constitution of Brazilian Political Sciences. It aims to identify the traditions that influenced the perceptions of intellectual groups, sociologists and political scientists responsible for the principles that structured the discipline’s current production. From interviews and literature review, we identified traditions and their oppositions. We understand that the adherence and the incorporation of one or another tradition by one of the groups involved depended on their academic trajectories, marked by oppositions oriented in the sense of defining the discipline i.e. defining the legitimate objective of the field and the approaches considered more appropriate to study it. The production depended on three groups and perceptions: (I) humanistic, associated with intellectuals that studied political themes before the institutionalization of the Political Sciences; (ii) academic-societal, associated with the “São Paulo’s sociological school”; and (iii) scientific-politico-logical, associated with the group constituted around the UFMG (Federal University of Minas Gerais) and the Iuperj (University Research Institute of Rio de Janeiro), responsible for the institutionalization of the Political Sciences in Brazil. Key words: Brazilian Political Sciences; Social Scientists; Academic productions; Disciplinary traditions; Intellectual traditions TRADITIONS DISCIPLINAIRES ET TRADITIONS INTELLECTUELLES DANS LA TRAJECTOIRE DES SCIENCES POLITIQUES BRESILIENNES ABSTRACT L’article traite du rôle des traditions disciplinaires et intellectuelles dans la constitution des Sciences Politiques brésiliennes. L’objectif est d’identifier les traditions qui ont influencé l’opinion des groupes d’intellectuels, de sociologues et de politologues responsables des principes qui ont structuré la production actuelle de cette discipline. Suite aux interviews et références bibliographiques consultées, nous avons pu identifier les traditions et leurs oppositions. Cela nous a permis de comprendre que l’adhésion à telle ou telle tradition et son incorporation par les groupes concernés dépendaient de leurs trajectoires académiques marquées par des oppositions allant dans le sens de la définition de la discipline, c’est-à-dire de la définition de son objet légitime et des approches considérées les plus appropriées pour l’étudier. La production s’est faite en fonction de trois groupes et de points de vue : (i) humaniste, associée aux intellectuels qui étudiaient les thèmes politiques avant l’institutionnalisation des Sciences Politiques ; (ii) académique-sociétale, associée à “l’école sociologique de Sao Paulo”; et (iii) scientifique et politique, associée au groupe formé autour de l’UFMG et de l’Iuperj, responsables de l’institutionnalisation des Sciences Politiques au Brésil. Key words: Sciences Politiques brésiliennes; Chercheurs en sciences sociales; Production académique; Traditions disciplinaires; Traditions intellectuelles